La igualdad de nmeros racionales - Vsquez Snchez, Rigoberto (2020)
Equality is a relationship that is defined between numbers. The three most important properties of equality are summarized in a mathematical structure known as an equivalence relationship. But mathematics goes far beyond "its application", although the various practical purposes have influenced its development, its very intrinsic interest has been fundamental in it. The development of theoretical and applied mathematics are certainly interrelated, multiple mathematical theoretical developments have allowed to model and advance in fields of the natural or social sciences, also the need to solve practical problems humanity has driven important discoveries of theoretical mathematics. It is therefore extremely important to present situations and contexts that allow the student to modify his conceptions and begin to understand the true nature of mathematics; situations, that allow them to move forward from the level of solving problems pragmatic or every day to understand mathematics itself. This type of context can be found, for example, in geometry, geometric demonstrations of arithmetic or algebraic properties allow transcending the meanings of equality and equivalence in routine contexts linked exclusively to clearly operational and day-to-day problems.